2015
DOI: 10.1042/cs20150154
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of function, growth and survival of GLP-1-producing L-cells

Abstract: Glucagon-like peptide-1 (GLP-1) is a peptide hormone, released from intestinal L-cells in response to hormonal, neural and nutrient stimuli. In addition to potentiation of meal-stimulated insulin secretion, GLP-1 signalling exerts numerous pleiotropic effects on various tissues, regulating energy absorption and disposal, as well as cell proliferation and survival. In Type 2 Diabetes (T2D) reduced plasma levels of GLP-1 have been observed, and plasma levels of GLP-1, as well as reduced numbers of GLP-1 producin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 197 publications
0
26
0
Order By: Relevance
“…GLP‐1 is a powerful hormone whose ability to stimulate insulin secretion and normalize glucose levels has been widely documented, and GLP‐1 levels increase after bariatric surgery . Surprisingly, it has been reported that the GLP‐1 receptor is not required for the therapeutic effects of bariatric surgeries .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GLP‐1 is a powerful hormone whose ability to stimulate insulin secretion and normalize glucose levels has been widely documented, and GLP‐1 levels increase after bariatric surgery . Surprisingly, it has been reported that the GLP‐1 receptor is not required for the therapeutic effects of bariatric surgeries .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the activation of TGR5 by the selective agonist INT‐777 triggers an increase in glucagon‐like peptide‐1 (GLP‐1) secretion in enteroendocrine L cells of the intestinal epithelium . This incretin gut hormone modulates insulin secretion and sensitivity, glucagon secretion, and β cell mass, thus improving glucose homeostasis . In light of these findings, we hypothesized that the activation of BA signaling, through its receptor TGR5, contributes to the insulin‐sensitizing effects of VSG surgery.…”
mentioning
confidence: 99%
“…; Gribble and Reimann ; Kuhre et al. ). For instance, the high concentration of these peptides in the colon raises the question whether a similarly large secretion can be elicited from this part of the gut.…”
Section: Introductionmentioning
confidence: 99%
“…GLP-1 plays an important role in the regulation of glucose homeostasis via actions including increasing glucose-dependent insulin secretion, proinsulin gene expression, and β-cell proliferation and anti-apoptotic signaling 31. Therefore, we investigated the in vivo effects of triamterene on STZ-induced diabetic rats.…”
Section: Discussionmentioning
confidence: 99%